Efficacy and safety of intravesical instillation of KRP‐116D (50% dimethyl sulfoxide solution) for interstitial cystitis/bladder pain syndrome in Japanese patients: A multicenter, randomized, double‐blind, placebo‐controlled, clinical study. (12th February 2021) - Yoshimura, Naoki; Homma, Yukio; Tomoe, Hikaru; Otsuka, Atsushi; Kitta, Takeya; Masumori, Naoya; Akiyama, Yoshiyuki; Niimi, Aya; Mitsui, Takahiko; Nanri, Masaharu; Namima, Takashige; Takei, Mineo; et al.
Abstract : Objective: To evaluate the efficacy and safety of intravesical KRP‐116D, 50% dimethyl sulfoxide solution compared with placebo, in interstitial cystitis/bladder pain syndrome patients. Methods: Japanese interstitial cystitis/bladder pain syndrome patients with an O'Leary‐Sant Interstitial Cystitis Symptom Index score of ≥9, who exhibited the bladder‐centric phenotype of interstitial cystitis/bladder pain syndrome diagnosed by cystoscopy and bladder‐derived pain, were enrolled. Patients were allocated to receive either KRP‐116D ( n = 49) or placebo ( n = 47). The study drug was intravesically administered every 2 weeks for 12 weeks. Results: For the primary endpoint, the change in the mean O'Leary‐Sant Interstitial Cystitis Symptom Index score from baseline to week 12 was −5.2 in the KRP‐116D group and −3.4 in the placebo group. The estimated difference between the KRP‐116D and placebo groups was −1.8 (95% confidence interval −3.3, −0.3; P = 0.0188). Statistically significant improvements for KRP‐116D were also observed in the secondary endpoints including O'Leary‐Sant Interstitial Cystitis Problem Index score, micturition episodes/24 h, voided volume/micturition, maximum voided volume/micturition, numerical rating scale score for bladder pain, and global response assessment score. The adverse drug reactions were mild to moderate, and manageable. Conclusions: This first randomized, double‐blind, placebo‐controlled trial shows that KRP‐116D improves symptoms, voiding parameters, and global response assessment, compared with placebo, and has a well‐tolerated safety profile in interstitial cystitis/bladder pain syndrome patients with the bladder‐centric phenotype.